2018
DOI: 10.1002/oca.2441
|View full text |Cite
|
Sign up to set email alerts
|

Inverse optimal control for asymptotic trajectory tracking of discrete‐time stochastic nonlinear systems in block controllable form

Abstract: This paper concerns an inverse optimal control-based trajectory tracking of discrete-time stochastic nonlinear systems. It is assumed that the nonlinear system can be transformed to the so called nonlinear block controllable form.Additionally, the synthesized control law minimizes a cost functional, which is posteriori determined. In contrast to the optimal control technique, this scheme avoids to solve the stochastic Hamilton-Jacobi-Bellman equation, which is not an easy task. Based on a discrete-time stochas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…While the inverse optimal control approach has been explored for the discrete‐time version, 36‐38 an impulsive approach that provides a sudden change at j$$ j $$th instants of the k$$ k $$th time steps of the discrete‐time system is needed. Impulsive systems can be pivotal for scheduling therapies in different diseases such as HIV infection, 29,33,39‐41 influenza infection, 28,42 diabetes 43 as well as vaccination 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the inverse optimal control approach has been explored for the discrete‐time version, 36‐38 an impulsive approach that provides a sudden change at j$$ j $$th instants of the k$$ k $$th time steps of the discrete‐time system is needed. Impulsive systems can be pivotal for scheduling therapies in different diseases such as HIV infection, 29,33,39‐41 influenza infection, 28,42 diabetes 43 as well as vaccination 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Impulsive control is particularly important when a system cannot be controlled by a continuous input, in other words if the input can only be applied at some jth instants of the kth time steps of the discrete-time system, this is also known in the literature as Markov jump systems. [33][34][35] While the inverse optimal control approach has been explored for the discrete-time version, [36][37][38] an impulsive approach that provides a sudden change at jth instants of the kth time steps of the discrete-time system is needed. Impulsive systems can be pivotal for scheduling therapies in different diseases such as HIV infection, 29,33,[39][40][41] influenza infection, 28,42 diabetes 43 as well as vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…e applications of the inverse optimal control method on Quanser 2 DOF helicopters and unmanned aerial helicopters can be found in references [36,37]. It can be found that the methods above mainly address the stabilization problem of the nonlinear systems.…”
Section: Introductionmentioning
confidence: 99%